Diversity of Orchid species in the Tilu Mountains Region of Indonesia and the Potential for Phytochemistry - Prapitasari, Bela; Rezaldi, Taufiq; Kenza, Masfufah Lutvita; Aliwafa, Ahmad; Gunawan, Dwi Ariya; Nuraini, Latifa (Journal of Tropical Biodiversity and Biotechnology, 2024)
Orchids are one of the largest and globally distributed plant families. Indonesia has the most types of orchids, estimated around 20% from the total species across the world. Mainly orchids used as an ornamental plant. This research aimed to elucidate another potential of orchids as possibly for herbal medicine plant. The potential of orchids as herbal medicine has been known for a long time, but there is lack of well-documented research. The research method used in this research is exploration on predetermined research sites that were conducted in Mount Tilu, West Java on 2022. Observation data of orchids were collected on the sites and the analysis was carried out in a qualitative descriptive approach by describing the data from the research results and comparisons were made through a literature review. Based on the research results, we found about 31 species from 28 genera consisting of 24 epiphytic orchids and 7 terrestrial orchids in the Mount Tilu Kuningan area, West Java. There are 4 endemic species categorised in Java; Chilochista javanica, Crepidium koordesii, Crepidium junghuhnii, and Taeniophyllum biocellatum.